Using SPSS for Windows and Macintosh : (Pearson/Prentice Hall, 2005)
The development of easy-to-use statistical software like SPSS has changed the way statistics is being taught and learned. Even with these advancements, however, students sometimes still find statistics a tough nut to crack. Using SPSS for Windows and Macintosh, 7/e, guides students through basic SPSS techniques using step-by-step descriptions and explaining in detail how to avoid common pitfalls in the study of statistics.